Pengaruh Daya Tarik Produk, Harga dan Suasana Pasar Terhadap Keputusan Pembelian dengan Kepuasan Pelanggan sebagai Variabel Mediasi - Nugroho, Irfan Afianto; Muslikh, Muslikh (Journal of Economics and Business Aseanomics, 2023)
Analyzing purchasing decisions influenced by several variables: product attractiveness, price and store atmosphere mediated by customer satisfaction is the aim of this research on a remote car (battery car) game rental business called 2 Putri Toys located at Koja Baru Market, North Jakarta. The SEM data analysis technique uses PLS. The respondents to this survey were 2 Putri Toys customers, totaling 107 random respondents. From the results of SmartPLS3 data, it was found that there was a positive and significant influence between product attractiveness and price on customer satisfaction. Product attractiveness has a positive and significant effect on purchasing decisions. Purchasing decisions are influenced by price and customer satisfaction positively and not significantly. The store atmosphere has a negative and significant effect on purchasing decisions but has a positive and insignificant effect on customer satisfaction. Although customer satisfaction cannot influence market conditions regarding purchasing decisions, product attractiveness and price can be influenced.